Credibility : how leaders gain and lose it, why people demand it - Kouzes, James M., 1945- 4 0 16; Posner, Barry Z.; 5 (San Francisco, California : Jossey-Bass Publishers, 2003)
Explains that effective leadership is above all a relationship, with credibility as the cornerstone, and reveals the six key disciplines and related practices that strengthen a leader's capacity for developing and sustaining credibility.
Includes bibliographical references and indexes.
Adult.
Keywords: 2 -- 0; 6; Leadership.;Executive ability.;Interpersonal relations. -- 20; 20; 2